Hybrid Learning Development: A Combination of Level of Inquiry and Moodle to Enhance Students' Critical Thinking Skills - Saidil Mursali; Ika Nurani Dewi; Zul Anwar (Al Jahiz, 2025)
Higher education currently faces significant challenges in integrating information and communication technology (ICT) into the learning process and equipping students with Critical Thinking Skills. However, in the post-pandemic era, many universities rarely incorporate ICT into their teaching, and students' critical thinking abilities still need improvement. Hybrid Learning, which combines Level of Inquiry (LoI) and Modular Object-Oriented Dynamic Learning Environment (Moodle), can be an effective solution to address these issues. The combination of LoI and Moodle creates a learning environment that allows students to engage in independent and collaborative learning while developing skills through investigative activities. The aim of this research is to develop Hybrid Learning that integrates LoI and Moodle to enhance students' Critical Thinking Skills. This research employs an instructional development model by Fenrich, which includes: Analysis, Planning, Design, Development, Implementation, and Evaluation and Revision. The implementation stage utilizes a pre-experimental research design with a One Group Pretest-Posttest Design conducted at the Faculty of Science and Applied Technology at Undikma. The research instruments consist of validation sheets and critical thinking skill tests. Data analysis is conducted using quantitative descriptive methods and n-Gain tests. The results indicate that the developed Hybrid Learning model combining LoI and Moodle is valid and reliable for use in the learning process. The validation scores for the Syllabus (3.9), Lesson Plans (3.9), Student Worksheets (3.8), and Critical Thinking Skills tests (3.9). Additionally, the Hybrid Learning combining LoI and Moodle are effective in significantly improving students' Critical Thinking Skills.